A Q-Theory of Banks - Begenau, Juliane; Bigio, Saki; Majerovitz, Jeremy; Vieyra, Matias (Review of Economic Studies, 2026)
Abstract Bank capital requirements are based on book values, which are slow to reflect losses. In this article, we develop a dynamic model of banks to study the interaction of regulation and delayed accounting. Our model explains four stylized facts: book and market values diverge during crises, the market-to-book ratio predicts future profitability, book leverage constraints rarely bind strictly even as market leverage fans out during crises, and banks delever gradually after net-worth shocks. We show how delayed accounting can allow the regulator to achieve better outcomes than immediate (mark-to-market) accounting. In an estimated version of the model, the optimal regulation couples faster loan-loss recognition with a modest relaxation of the book leverage constraint.